THE REFORM OF CRIMINAL JUSTICE WILL CONTINUE - Krastiņš, Uldis (Administrative and Criminal Justice, 2015)
The article substantiates the view that approved on the 9th of January 2009 by the Cabinet of Ministers of the Latvian Republic, the concept of policy of criminal penalties and adopted on the 13th of December 2013 by the Saeima, the numerous changes in the Criminal Law (CL), should be considered as the beginning of the reform of criminal law of Latvia. In particular, in CL, now is written the principle non bis in idem, the prohibited analogy in the criminal law, from the criminal law is excluded the institute of repetition of criminal acts in all its forms and thereby the scope of application of real set of acts. The author of the article points out that were developed also the other draft amendments and supplements in the CL, for example, regarding the special confiscation of property, the expansion of the content of the estimating concept of essential damage, the other interpretation of criminal acts in the road traffic is suggested, as well as the other forms of guilt in the criminal acts with the complex composition.